Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.desal.2018.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Serially connected forward osmosis membrane elements of pressure-assisted forward osmosis-reverse osmosis hybrid system: Process performance and economic analysis

Abstract: Pressure-assisted forward osmosis (PAFO) has been considered an alternative of forward osmosis (FO) process to reduce capital expenditure (CAPEX) of FO. This is mainly attributed to the enhanced water flux through the FO membranes which leads to the improved dilution of draw streams. In this regard, it has been expected that employing PAFO in the FO-reverse osmosis (RO) hybrid system for seawater desalination can reduce the overall economics of the hybrid process. However, replacing FO with PAFO causes an addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…While the above-mentioned parameters are useful to describe module performance, they do not explicitly address the economic impacts of energy consumption, especially for a large-scale system. Despite previous studies having evaluated the economic impacts [ 144 , 145 , 146 ] or total cost [ 147 ] of large-scale desalination systems, only a handful of studies have evaluated the impact of spacer design on total cost [ 148 ]. A recent techno-economic study by Toh et al [ 149 ] found that improving spacer design is more crucial than increasing permeance at same recovery, especially for SWRO systems.…”
Section: Module Performance Metricsmentioning
confidence: 99%
“…While the above-mentioned parameters are useful to describe module performance, they do not explicitly address the economic impacts of energy consumption, especially for a large-scale system. Despite previous studies having evaluated the economic impacts [ 144 , 145 , 146 ] or total cost [ 147 ] of large-scale desalination systems, only a handful of studies have evaluated the impact of spacer design on total cost [ 148 ]. A recent techno-economic study by Toh et al [ 149 ] found that improving spacer design is more crucial than increasing permeance at same recovery, especially for SWRO systems.…”
Section: Module Performance Metricsmentioning
confidence: 99%
“…The energy penalty posed by the pressureassisted operational mode could potentially be compensated by enhanced permeate throughput and reduced membrane area [20]. The economic potential of integrated PAFO-RO has been proven higher than integrated FO-RO process, though the plausibility of implementing PAFO to existing RO plants still remain uncertain due to the additional capital expenses associated with PAFO [21].…”
Section: Fig 2 Integrated Fo-ro Process For Seawater Desalinationmentioning
confidence: 99%
“…A diamond-type mesh spacer was adopted for the feed channel (1.15 mm), and a combination of tricot-type and diamond-type spacers was adopted for the draw channel (1.98 mm). The detailed configuration of the spiral-wound FO element can be found elsewhere [41].…”
Section: Spiral-wound Fo Membranesmentioning
confidence: 99%